A Model for Incorporating Patient and Stakeholder Voices in a Learning Healthcare Network: Washington State’s Comparative Effectiveness Research Translation Network (CERTAIN) - Devine, EB (2013)
OBJECTIVE: To describe the inaugural comparative effectiveness research (CER) cohort study of Washington State’s Comparative Effectiveness Research Translation Network (CERTAIN), which compares invasive to non-invasive treatments for peripheral artery disease; to focus on the patient-centeredness of this cohort study by describing it within the context of a newly published conceptual frameworks for patient-centered outcomes research (PCOR). STUDY DESIGN AND SETTING: The peripheral artery disease study was selected due to clinician-identified uncertainty in treatment selection and differences in desired outcomes between patients and clinicians. Patient-centeredness is achieved through the ‘Patient Voices Project’, a CERTAIN initiative through which patient-reported outcome (PRO) instruments are administered for research and clinical purposes, and a study-specific patient advisory group where patients are meaningfully engaged throughout the life cycle of the trial. A clinician-led research advisory panel follows in parallel. RESULTS: Primary outcomes are PRO instruments that measure function, health-related quality of life, and symptoms; the latter developed with input from patients. Input from the patient advisory group led to revised retention procedures, which now focus on short-term (3–6 months) follow-up. The research advisory panel is piloting a point-of-care, patient assessment checklist, there by returning study results to practice. The cohort study is aligned with the tenets of one of the new conceptual frameworks for conducting PCOR. CONCLUSION: CERTAIN’s inaugural cohort study may serve as a useful model for conducting PCOR and creating a Learning Healthcare Network.